(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article reveals that pedagogical intuition is manifested in the harmony of the personal and professional qualities of the coach, allows for quick and effective action in unexpected situations, and the multifaceted role of intuition in coaching. It also highlights the important functions of pedagogical intuition in coaching.